Taxation as a driver for Portuguese foreign direct investment in Netherlands: myth or reality? - Pereira, Ana Catarina Gonçalves (2019)
Together with the increased internationalization of the companies, as an answer to the challenges of globalization, emerged the interaction between different tax systems. In this context, MNCs exploited gaps and differences between tax systems in order to reduce the tax burden. As a result, the taxation became an area of attention and highly considered as a key factor in the decision of internationalization. The present study aims to identify the countries where the Portuguese companies normally invest, and how taxation influence that decision of investment. With this objective, a comparative analysis between the Portuguese tax system and the tax system of the country where the Portuguese companies more invest in was made. It was also made a financial analysis to a set of Portuguese companies with presence in that country, in order to analyse the nature of its activities, the functions performed, the assets owned and the risks assumed by those companies. The results allowed to identify the existence of differences in Portuguese taxation regime and the Dutch tax regime, namely regarding the business profits, capital gains, dividends and interests/loans. Finally, it was possible to conclude that the tax regime assumes a great importance for the investment decision. However, it was possible to conclude that the investment of the companies analysed does not correspond to genuine FDI, but to the creation of SPEs, which in turn were platforms for the investment and internalisation of the group, allowing the group benefit from the advantages of the Dutch tax regime.